Synthesis of new enantiopure poly(hydroxy)aminooxepanes as building blocks for multivalent carbohydrate mimetics - Bouché, Léa; Kandziora, Maja; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2014)
New compounds with carbohydrate-similar structure (carbohydrate mimetics) are presented in this article. Starting from enantiopure nitrones and lithiated TMSE-allene we prepared three 1,2-oxazine derivatives which underwent a highly stereoselective Lewis acid-induced rearrangement to give bicyclic products in good yield. Subsequent reductive transformations delivered a library of new poly(hydroxy)aminooxepane derivatives. The crucial final palladium-catalyzed hydrogenolysis of the 1,2-oxazine moiety was optimized resulting in a reasonably efficient approach to a series of new seven-membered carbohydrate mimetics.
Keywords: aminooxepanes; carbohydrate mimetics; hydrogenolyses; Lewis acid-induced; lithiated allenes; nitrones; 1,2-oxazines; rearrangements; reductions

Carbohydrate-based Drug Discovery - Wong, C.-H. (Wiley-VCH, 2003)

(untitled) - Sears, P.; Wong, C.-H. (Angew. Chem., 1999)
Angew. Chem., Int. Ed. 1999, 38, 2300-2324. doi:10.1002/(SICI)1521-3773(19990816)38:16<2300::AID-ANIE2300>3.0.CO;2-6

(untitled) - Koester, D. C.; Holkenbrink, A.; Werz, D. B. (Synthesis, 2010)

(untitled) - Lee, Y. C.; Lee, R. T. (Acc. Chem. Res., 1995)

(untitled) - Lundquist, J. J.; Toone, E. J. (Chem. Rev., 2002)

(untitled) - Kakinuma, K.; Ikekawa, N.; Nakagawa, A.; Omura, S. (J. Am. Chem. Soc., 1979)

(untitled) - Funel-Le Bon, C.; Berrué, F.; Thomas, O. P.; Reyes, F.; Amade, P. (J. Nat. Prod., 2005)

Advances in Carbohydrate Chemistry and Biochemistry - Saha, J.; Peczuh, M. W. (Synthesis and properties of septanose carbohydrates, 2011)

(untitled) - Sahabuddin, S.; Roy, A.; Drew, M. G. B.; Roy, B. G.; Achari, B.; Mandal, S. B. (J. Org. Chem., 2006)

(untitled) - Tripathi, S.; Roy, B. G.; Drew, M. G. B.; Achari, B.; Mandal, S. B. (J. Org. Chem., 2007)

(untitled) - Bhattacharjee, A.; Datta, S.; Chattopadhyay, P.; Ghoshal, N.; Kundu, A. P.; Pal, A.; Mukhopadhyay, R.; Chowdhury, S.; Bhattacharjya, A.; Patra, A. (Tetrahedron, 2003)

(untitled) - Hoberg, J. O. (Tetrahedron, 1998)

(untitled) - Kotkar, D.; Ghosh, P. K. (J. Chem. Soc., Chem. Commun., 1986)

(untitled) - Pavlik, C.; Onorato, A.; Castro, S.; Morton, M.; Peczuh, M. W.; Smith, M. B. (Org. Lett., 2009)

(untitled) - Snyder, N. L.; Haines, H. M.; Peczuh, M. W. (Tetrahedron, 2006)

(untitled) - Peczuh, M. W.; Snyder, N. L. (Tetrahedron Lett., 2003)

(untitled) - Castro, S.; Johnson, C. S.; Surana, B.; Peczuh, M. W. (Tetrahedron, 2009)

Heterocycles in Natural Product Synthesis - Riley, D. L.; van Otterlo, W. A. L. (Oxepines and Azepines, 2011)
See for a recent review about oxepines in natural product synthesis.

(untitled) - Fyvie, W. S.; Morton, M.; Peczuh, M. W. (Carbohydr. Res., 2004)

(untitled) - Wong, J. C. Y.; Lacombe, P.; Sturino, C. F. (Tetrahedron Lett., 1999)

(untitled) - Ganesh, N. V.; Jayaraman, N. (J. Org. Chem., 2007)

(untitled) - Ganesh, N. V.; Jayaraman, N. (J. Org. Chem., 2009)

(untitled) - Al-Harrasi, A.; Reissig, H.-U. (Angew. Chem., 2005)
Angew. Chem., Int. Ed. 2005, 44, 6227-6231. doi:10.1002/anie.200501127

(untitled) - Al-Harrasi, A.; Pfrengle, F.; Prisyazhnyuk, V.; Yekta, S.; Koóš, P.; Reissig, H.-U. (Chem.–Eur. J., 2009)

(untitled) - Pfrengle, F.; Reissig, H.-U. (Chem.–Eur. J., 2010)

(untitled) - Pfrengle, F.; Lentz, D.; Reissig, H.-U. (Angew. Chem., 2009)
Angew. Chem., Int. Ed. 2009, 48, 3165-3169 doi:10.1002/anie.200805724

(untitled) - Pfrengle, F.; Reissig, H.-U. (Chem. Soc. Rev., 2010)

(untitled) - Bouché, L.; Reissig, H.-U. (Pure Appl. Chem., 2012)

(untitled) - Dondoni, A.; Franco, S.; Junquera, F.; Merchán, F. L.; Merino, P.; Tejero, T. (Synth. Commun., 1994)

(untitled) - Dondoni, A.; Franco, S.; Junquera, F.; Merchán, F. L.; Merino, P.; Tejero, T.; Bertolasi, V. (Chem.–Eur. J., 1995)

(untitled) - Helms, M.; Schade, W.; Pulz, R.; Watanabe, T.; Al-Harrasi, A.; Fišera, L.; Hlobilová, I.; Zahn, G.; Reissig, H.-U. (Eur. J. Org. Chem., 2005)

(untitled) - Brasholz, M.; Reissig, H.-U.; Zimmer, R. (Acc. Chem. Res., 2009)

(untitled) - Dernedde, J.; Enders, S.; Reissig, H.-U.; Roskamp, M.; Schlecht, S.; Yekta, S. (Chem. Commun., 2009)

(untitled) - Roskamp, M.; Enders, S.; Pfrengle, F.; Yekta, S.; Dekaris, V.; Dernedde, J.; Reissig, H.-U.; Schlecht, S. (Org. Biomol. Chem., 2011)

(untitled) - Abushanab, E.; Vemishetti, P.; Leiby, R. W.; Singh, H. K.; Mikkilineni, A. B.; Wu, D. C.-J.; Saibaba, R.; Panzica, R. P. (J. Org. Chem., 1988)

New Transformations of Enantiopure 3,6-Dihydro-2H-1,2-oxazines: Ring Cleavages, Ring Enlargements and a Novel Approach to Carbohydrate Mimetics - Al-Harrasi, A. (Freie Universität Berlin, 2005)

(untitled) - Dondoni, A.; Junquera, F.; Merchan, F. L.; Merino, P.; Tejero, T. (Synthesis, 1994)

(untitled) - Merino, P.; Lanaspa, A.; Merchan, F. L.; Tejero, T. (J. Org. Chem., 1996)

(untitled) - Fujiwara, K.; Amano, A.; Tokiwano, T.; Murai, A. (Tetrahedron, 2000)

(untitled) - Phillips, A. J.; Morris, J. C.; Abell, A. D. (Tetrahedron Lett., 2000)

(untitled) - Moinizadeh, N.; Klemme, R.; Kansy, M.; Zimmer, R.; Reissig, H.-U. (Synthesis, 2013)
See for Click reactions using 1,2-oxazines which were recently described by our group.

(untitled) - Lal, B.; Pramanik, B. N.; Manhas, M. S.; Bose, A. K. (Tetrahedron Lett., 1977)

(untitled) - Bressel, B.; Egart, B.; Al-Harrasi, A.; Pulz, R.; Reissig, H.-U.; Brüdgam, I. (Eur. J. Org. Chem., 2008)

(untitled) - Jasiński, M.; Lentz, D.; Moreno-Clavijo, E.; Reissig, H.-U. (Eur. J. Org. Chem., 2012)

(untitled) - Al-Harrasi, A.; Brüdgam, I.; Hartl, H.; Reissig, H.-U. (Z. Kristallogr. NCS, 2006)
See for an X-ray analysis of the corresponding TBS-protected oxepane of 27.

Heterogeneous Catalysis in Organic Chemistry - Smith, G. V.; Notheisz, F. (Hydrogenolysis of Benzyl-Nitrogen Bonds, 1999)

(untitled) - Fu, X.; Cook, J. M. (J. Am. Chem. Soc., 1992)

(untitled) - Fu, X.; Cook, J. M. (J. Org. Chem., 1993)

(untitled) - Su, J.-K.; Jia, Y.-M.; He, R.; Rui, P.-X.; Han, N.; He, X.; Xiang, J.; Chen, X.; Zhu, J.; Yu, C.-Y. (Synlett, 2010)